Hydrocephalus and moderate mental retardation in a boy with Van der Woude phenotype and IRF6 gene mutation - Zechi-Ceide, Roseli Maria; Guion-Almeida, Maria Leine; de Oliveira Rodini, Elaine Sbroggio; Jesus Oliveira, Nelio Alessandro; Passos-Bueno, Maria Rita (Lippincott Williams & Wilkins, 2007)
In this report, we present a boy with lower lip pits, distinct craniofacial dysmorphism with cleft lip and palate, central nervous system malformation, and severe mental retardation. Similar but less pronounced facial findings were present in his mentally normal mother and maternal grandfather, both presenting with lower lip pits. Cleft lip was present in patient's father. Analysis of the VWS1 and VWS2 regions were performed to elucidate the molecular basis of the phenotype of the propositus. Screening or mutations at the IRF6 gene detected a pathogenic mutation (c.960G > C) in the propositus and in his mother; and a single nucleotide polymorphism (c.175-5C > G) in the propositus and in his father. Clinical and genetic aspects of this case are discussed.
Keywords: central nervous system malformation; cleft lip and palate; IRF6 gene; lower lip pits; Van der Woude syndrome